HIV voluntary counseling and testing practices among military personnel and civilian residents in a military cantonment in southeastern Nigeria - Azuogu BN (Dove Medical Press, 2011)
BN Azuogu, LU Ogbonnaya, CN Alo Communicable Diseases Control Research Centre, Department of Community Medicine, Ebonyi State University Teaching Hospital, Abakaliki, Nigeria Background: Voluntary counseling and testing (VCT) services are expected to lower rates of HIV transmission through a reduction in high-risk sexual behavior and through improved access to medical treatment, care, and support. However, increasing access to and uptake of VCT, especially among groups at high risk for HIV infection, has remained a major challenge in Africa. Purpose: The study was undertaken to determine the uptake of VCT (measured by whether study participants had ever received an HIV test) and the factors influencing this practice among military and civilian residents of a military cantonment in Abakaliki, southeastern Nigeria. Methods: A cross-sectional descriptive survey of all cantonment residents aged between 20 and 64 years was conducted. A multistage sampling technique was used to establish the sample size; data were collected from 350 military and civilian cantonment residents using a pretested questionnaire. Data were analyzed using SPSS software (v 16.0; SPSS Inc, Chicago, IL) and the significance of any association was tested at P < 0.05 using the chi-square statistic. Results: One hundred and forty-five (41.4%) respondents reported having ever been tested for HIV; however, only 44 (12.6%) respondents had received the test between 4 and 12 months prior to the survey period. Some of the significant factors that positively influenced uptake of VCT were awareness of VCT (P < 0.001), education level (P < 0.006), and knowledge of antiretroviral therapy benefits (P < 0.01). Conclusion: The uptake of VCT by the residents of the cantonment was low. The establishment of VCT services in the cantonment is urgently recommended, together with the targeting of high-risk population groups in HIV/AIDS and VCT information dissemination efforts. Keywords: VCT uptake, HIV test, most-at-risk population (MARP), people living with HIV/AIDS (PLWHAs)